Hubungan keberkesanan latihan dengan prestasi kerja - Abdul Kadir, Abdul Latif; Ismail, Maimunah (Universiti Putra Malaysia Press, 1997)
This study aims to evaluate the training effectiveness and its relationship with the job performance of newly appointed customs officers who have undergone the Program Pengajian Asas Operasi Perkastaman (PPAOP) course at Royal Customs Academy (RCAM), Melaka. Data were gathered from 84 respondents using self administered questionnaires. Correlation analysis revealed that training seems to have a positive relationship with post training job performance. The study also showed there was a significant positive relationship between pre- and post-training job performance. The study showed that RCAM plays its role effectively in developing competent officers. It is suggested that RCAM should pay serious attention to the quality of methodology and teaching aids, facilitators, customs module and management module especially contents, methodology and teaching techniques.